Implementation of OSI Layer Based on Interactive Education Media - Chairul Imam; Muhammad Furqon Siregar; Auliana Nasution (Jurnal Mantik, 2021)
The design of basic network learning media using computer technology based on interactive educational media aims to facilitate the introduction of basic networks using interactive educational media so that they are more interested and able to follow and pay attention to the explanation conveyed through an OSI Layer work process in learning the basic network. In order to make it easier for readers, and faster to master and be able to practice for students who want to learn about the basic network introduction to the OSI Layer.